2010
DOI: 10.1074/jbc.m109.040634
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimerization of ORL1 and Opioid Receptors and Its Consequences for N-type Calcium Channel Regulation

Abstract: We have investigated the heterodimerization of ORL1 receptors and classical members of the opioid receptor family. All three classes of opioid receptors could be co-immunoprecipitated with ORL1 receptors from both transfected tsA-201 cell lysate and rat dorsal root ganglia lysate, suggesting that these receptors can form heterodimers. Consistent with this hypothesis, in cells expressing either one of the opioid receptors together with ORL1, prolonged ORL1 receptor activation via nociceptin application resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 47 publications
4
79
0
9
Order By: Relevance
“…Similarly, a Ca v 2.2-opioid receptor like-1 (ORL-1; also known as nociception receptor) signaling complex has been documented in small DRG neurons, and supports a tonic agonist-independent G protein inhibition of the Ca 21 channel evidenced by prepulse facilitation (Beedle et al, 2004). Similar observations have been reported for m-and d-opioid receptors transiently expressed with Ca v 2.2 channel in tsA201 cells, although the existence of these protein complexes remains to be explored in native conditions (Chee et al, 2008;Evans et al, 2010). Also, a physical interaction exists between Ca v 2.2 channels and dopamine D1 and D2 receptors and requires other channel structural determinants, including the II-III intracellular linker Kisilevsky and Zamponi, 2008;Weiss, 2009).…”
Section: Voltage-independent Inhibition Of Ca V 2 Channelssupporting
confidence: 61%
See 2 more Smart Citations
“…Similarly, a Ca v 2.2-opioid receptor like-1 (ORL-1; also known as nociception receptor) signaling complex has been documented in small DRG neurons, and supports a tonic agonist-independent G protein inhibition of the Ca 21 channel evidenced by prepulse facilitation (Beedle et al, 2004). Similar observations have been reported for m-and d-opioid receptors transiently expressed with Ca v 2.2 channel in tsA201 cells, although the existence of these protein complexes remains to be explored in native conditions (Chee et al, 2008;Evans et al, 2010). Also, a physical interaction exists between Ca v 2.2 channels and dopamine D1 and D2 receptors and requires other channel structural determinants, including the II-III intracellular linker Kisilevsky and Zamponi, 2008;Weiss, 2009).…”
Section: Voltage-independent Inhibition Of Ca V 2 Channelssupporting
confidence: 61%
“…However, internalization of Ca v 2.2 channels is not accompanied by a diminution of the membrane Ca 21 current, questioning the physiologic relevance of this regulation (Murali et al, 2012). In addition, although m-opioid receptors also physically interact with Ca v 2.2 channels, they do not cointernalize, indicating that biochemical coupling of the channel with the GPCR is not sufficient to mediate agonist-mediated internalization of the Ca 21 channel (Evans et al, 2010). It is also possible that the assembly of Ca v 2 channels and GPCRs provides a mechanism that ensures spatiotemporal regulation of the Ca 21 entering synaptic nerve terminals.…”
Section: Voltage-independent Inhibition Of Ca V 2 Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphine also acts at m-opioid receptors that are expressed in the CNS (Diaz et al, 1995;Goodchild et al, 2004), where a clear correlation between physiologic effects and modulation of Ca V 2.2 channels is more difficult to establish. Although morphine is considered selective for m-opioid receptors, selective agonists of the other three members of the extended opioid receptor family (i.e., d-and k-opioid receptors, and nociceptin receptors) also functionally inhibit Ca V 2.2 channels (Gross and Macdonald, 1987;Moises et al, 1994;Motin et al, 1995;Morikawa et al, 1998;Toselli et al, 1999;Larsson et al, 2000;Yeon et al, 2004;Ruiz-Velasco et al, 2005;Evans et al, 2010). As in the case of m-opioid receptors, their activation induces analgesia in various animal models of pain (King et al, 1997;Darland et al, 1998;Field et al, 1999;Mika et al, 2001;Courteix et al, 2004;Nozaki et al, 2012).…”
Section: Ca V 2 Channel Pathophysiologymentioning
confidence: 99%
“…Numerous studies have shown that the MOP receptor is subjected to this type of regulation by interacting with a large number of GPCRs (25,26). In the case of MOP receptor dimerization with somatostatin sst 2A (27), substance P NK1 (28), ␣ 2a -adrenergic (29), and nociceptin ORL1 (30) receptors, cross-desensitization occurs and could result from co-internalization of both partners upon activation of only one receptor or from allosteric changes in binding affinity (31). However, in the case of NPFF 2 and MOP receptors previously shown to physically interact in SH-SY5Y cells (32), the stimulation of NPFF 2 receptors does not induce the internalization of MOP receptors but, conversely, partly blocks its trafficking (32).…”
mentioning
confidence: 99%